2019
DOI: 10.1002/jccs.201900081
|View full text |Cite
|
Sign up to set email alerts
|

Green, rapid, and highly efficient syntheses of α,α′‐bis[(aryl or allyl)idene]cycloalkanones and 2‐[(aryl or allyl)idene]‐1‐indanones as potentially biologic compounds via solvent‐free microwave‐assisted Claisen–Schmidt condensation catalyzed by MoCl5

Abstract: Green, rapid, and highly efficient syntheses of α,α 0 -bis [(aryl or allyl)idene]cycloalkanones and 2-[(aryl or allyl)idene]-1-indanones as potentially biologic compounds via solvent-free microwave-assisted Claisen-Schmidt condensation catalyzed by MoCl 5 Abstract A new, green, and highly efficient protocol for the expeditious preparation of some α,α 0 -bis[(aryl or allyl)idene]cycloalkanones and 2-[(aryl or allyl)idene]-1-indanones via a simple microwave-assisted Claisen-Schmidt condensation reaction catalyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 178 publications
0
6
0
Order By: Relevance
“…These two moieties were identified as the crucial interaction in acetylcholinesterase (AChE) inhibition [20,25] . The indanone moiety is also been studied as a drug moiety against other targets such as anti‐inflammatory, [26] other neurodegenerative/ neuroinflammation pathways, [27] and anti‐cancer properties [28] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two moieties were identified as the crucial interaction in acetylcholinesterase (AChE) inhibition [20,25] . The indanone moiety is also been studied as a drug moiety against other targets such as anti‐inflammatory, [26] other neurodegenerative/ neuroinflammation pathways, [27] and anti‐cancer properties [28] …”
Section: Introductionmentioning
confidence: 99%
“…[20,25] The indanone moiety is also been studied as a drug moiety against other targets such as anti-inflammatory, [26] other neurodegenerative/ neuroinflammation pathways, [27] and anti-cancer properties. [28] Although naturally existing phenolic compounds such as coumaric acid, caffeic acid, and sinapic acid in dietary supplements were studied to be beneficial to AD, [29][30][31][32] the studies of the possible synergism activity of phenolic moiety and existing drug fragment as an MTDL are still limited. [26][27][28] This study investigates the potential anti-AD MTDL of hybrids consisting of a donepezil fragment and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The compound, α α'‐bis‐(benzylidene) cyclohexanone is a widely used versatile pharmacophore [28] . The compound mentioned has been applied successfully for cytotoxicity studies, [29] cholesterol‐lowering, [30] HIV‐1 integrates inhibition, [31] cancer chemoprevention [32] and as antioxidant [33] . Also, some recent studies revealed the drug resistance reversal capability of bis‐benzylidene cyclohexanones [34,35] .…”
Section: Introductionmentioning
confidence: 99%
“…[28] The compound mentioned has been applied successfully for cytotoxicity studies, [29] cholesterol-lowering, [30] HIV-1 integrates inhibition, [31] cancer chemoprevention [32] and as antioxidant. [33] Also, some recent studies revealed the drug resistance reversal capability of bis-benzylidene cyclohexanones. [34,35] The potential of the compound has been extended to use as precursors to potentially bioactive pyrimidine derivatives, [36] bis-spiro pyrrolidines with antimicrobial and antifungal properties, [37] liquid-crystalline polymers, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our research program and because of consideration of all the points mentioned, herein we wish to report various environmentally benign, simple, and highly efficient strategies for the straightforward reduction of carboxylic acids to corresponding alcohols by employing four different types of cost-effective hydrogen donors namely sodium borohydride (NaBH 4 ), ammonium formate (HCO 2 NH 4 ), glycerol, and isopropanol ( i -PrOH) in the presence of Fe 3 O 4 @APTMS@ZrCp 2 Cl x ( x = 0, 1, 2) as a robust and durable magnetically nanocatalyst under neat conditions (Scheme ). It is worthwhile to note that to the best of our knowledge use of HCO 2 NH 4 and glycerol as a hydrogen donor (reducing agent) for the reduction of carboxylic acids to alcohols is reported for the first time.…”
Section: Introductionmentioning
confidence: 99%